Infantile hemangioma and cardiac defects: a puzzling association. A single center experience - Andrea Bassi; Andrea Azzarelli; Angelina Vaccaro; Carlo Mazzatenta (Mattioli1885, 2022)
BACKGROUND: Some studies have assessed the incidence of heart defects in children suffering from Infantile Hemangioma to be treated with propranolol, showing a possible higher prevalence of cardiac abnormalities in this group of patients. METHODS: We retrospectively reviewed clinical charts of children with infantile haemangiomas referred to our Dermatologic division from 2016 to 2021, who underwent our pediatric cardiology protocol screening before starting propranolol therapy. RESULTS: A total of 60 infants were enrolled. Electrocardiograms were available for all the patients and echocardiograpy for 50/60 (83.3%) children. Electrocardiogram didn't reveal any alterations in the large majority of cases (pathologic in 2/60, 3.3%) while echocardiograms revealed findings in 31/50 (51.7%) patients. Of these, persistent foramen ovale, which was found in 14/50 patients (28%), was considered as non-pathologic. Interatrial septal defects were the main pathological finding in 15/50 patients (30%), as single defect or in association with other abnormalities.    CONCLUSION: Our study confirms the presence of a higher rate of cardiologic findings in patients with infantile hemangioma evaluated before starting oral propranolol, compared to the known rate of those defects in healthy newborns. We also confirm that interatrial septal defects are the most frequent pathologic finding with a higher prevalence compared to published studies. Large prospective studies are needed to clarify a possible association of pathological cardiac findings in all patients with infantile hemangiomas and thereafter to evaluated the possible effect of propranolol therapy on these defects during time.